From evaluation to action: Merging dynamic evaluation and scaling readiness to advance the SNS scaling roadmap - Kirui, L.; Kihiu, E.; Kihoro, E.; Mudereri, B.T. (2025)
This document documents how dynamic evaluation and scaling readiness approaches were combined to advance the scaling roadmap of Rwanda’s Smart Nkunganire System (SNS), a national digital platform for agricultural input subsidies. Through participatory workshops and iterative reflection, stakeholders revisited earlier diagnoses, assessed what had changed, and refined the SNS innovation package. The process highlights how adaptive evaluation, system integration, and inclusive design can support responsible scaling of digital agriculture, improving efficiency, transparency, and resilience in national input delivery systems.